Arthroscopically Assisted Transposition of the Latissimus Dorsi in the Treatment of Patients with Massive Ruptures of the Rotator Cuff (Clinical Observation) - N. S. Ponomarenko; V. V. Monastyrev; I. A. Kuklin; D. V. Menshova (Acta Biomedica Scientifica, 2021)
Massive rotator cuff tears present a challenging problem for surgeons. According to various authors, from 10 to 40 % of ruptures are massive and more often affect patients over 60 years of age with low-intensity injuries. There is currently no consensus on the classification of rotator cuff injuries. The use of MRI is the gold standard in diagnostics and surgical tactics. Treatment of patients with severe fatty degeneration, muscular atrophy and retraction of the damaged tendon presents certain difficulties. Reinsertion of the damaged rotator cuff tendon is not possible in such patients. There are many different methods of surgical and conservative treatment. In our opinion, transposition of the latissimus dorsi is the method of choice for young and active patients. With the development of new technologies, transposition of the latissimus dorsi muscle began to be performed  arthroscopically. This article presents a clinical case: a woman with chronic total rupture of the supraspinatus tendon, Patte grade 3 and fatty degeneration of grade 3 by Thomazeau. The patient was also diagnosed with a secondary superior subluxation of the humeral head. The patient underwent surgical treatment: arthroscopic- associated transposition of the latissimus dorsi muscle to the greater tubercle of the humerus. There was a positive trend, an improvement in the functional result occurred already in the early postoperative period.  Considering the above, the method of choice in the treatment of patients with massive ruptures of the rotator cuff tendons can be considered as transposition of the latissimus dorsi muscle, performed by the arthroscopic-associated method.